PENGARUH MANAJEMEN LABA, STRUKTUR MODAL DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Witriyana, Yuvita Budi; Wahyuni, Ika; Widaninggar, Nanda (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The agricultural sector plays a crucial role in advancing Indonesia’s economy and enhancing foreign exchange earnings through labor absorption. This study aims to examine the influence of Earnings Management, Capital Structure and Company Growth on Firm Value with Profitability as an Intervening Variable in Agricultural Sector Companies Listed on the Indonesia Stok Exchange during 2020-2022. The research employs a quantitative method. This study’s data analysis and hypothesis testing utilize Structural Equation Modeling – Partial Least Square (PLS-SEM). The hypothesis results using indicate that Earnings Management significantly negatively impacts Profitability, Capital Structure has a positive but not significant impact on Profitability, while Company Growth has a negative but not significant impact on Profitability. Additionally, Earnings Management has a significant positive impact on Firm Value, Capital Structure has a positive but not significant impact on Firm Value, and Company Growth has a significant positive impact Firm Value, Profitability has a significant positive impact on Firm Value. The results of the indirect effects hypothesis testing show that Earnings Management has a negative but not significant impact on Firm Value through Profitability, Capital Structure has a positive but not significant impact on Firm Value through Profitability and Company Growth has a negative but not significant impact on Firm Value through Profitability.